Toward More-Than-Human Understandings of Sport and the Environment: A New Materialist Analysis of Everyday Fitness Practices - Julie E. Brice; Holly Thorpe (Frontiers Media S.A., 2021)
Sport and fitness have long been linked with healthy lifestyles, yet most sporting events and consumption practices are highly detrimental to the environment. While academics have examined the harmful effects of sporting mega-events and the production and consumption of sport equipment and clothing, there has been less engagement with the "mundane," everyday activities of consuming, laundering, and recycling of fitness objects. In this paper, we explore the potential in feminist new materialisms for rethinking the complex relationships between sport, fitness, and the environment. In particular, we explain how our engagement with Karen Barad's theory of agential realism led us to rethink women's habitual fitness practices as connected to environmental degradation. Working with Barad's concept of entanglement, we came to notice new human-clothing-environment relationships, focusing on how athleisure clothing itself is an active, vital force that intra-acts with other non-human (and human) matter within the environment. Adopting a diffractive methodology that included reading interviews with women about their activewear practices, our own experiences, new materialist theory, and environmental literature through each other, we focus on two examples that emerged through this process: laundering and disposal practices. Through these examples, we demonstrate the ways in which new materialisms encouraged us to move toward non-anthropocentric understandings of the sport-environment relationship and toward new ethical practices in our everyday fitness lifestyles.